Clinical and Demographic Characteristics of Patients With a New Diagnosis of Carriage or Clinical Infection With Carbapenemase-Producing Enterobacterales: A Retrospective Study - Adar, Assaf; Zayyad, Hiba; Azrad, Maya; Libai, Kozita; Aharon, Ilana; Nitzan, Orna; Peretz, Avi (Frontiers in Public Health, 2021)
Background: To examine the clinical, demographic and microbiologic characteristics of new rectal carbapenemase-producing carbapenem-resistant Enterobacterales (CP-CRE) carriers versus those with a clinical infection, hospitalized at Padeh-Poriya Medical Center between 2014-2017 and to examine the susceptibility profiles of isolates from clinical infections. Methods: In this retrospective, chart analysis, demographic and clinical data were collected from medical charts of 175 adult patients with either new- onset carbapenemase-producing Enterobacterales (CPE) carriage or clinical CPE infection. Collected data included age, ethnic group, place of residence, hospitalizations in the past 90 days, and 30-day mortality. Microbiological analyses considered bacterial genus, molecular resistance mechanism and antibiotic susceptibility. Results: A significantly higher percentage (42.4%) of CPE carriers were long-term care facility residents, and had been recently hospitalized (56.3%), as compared to patients with clinical CPE infection (29.2% and 45.9%, respectively). Additionally, we noted a high (58.3%) acquision of CPE in our hospital. The most common bacterial isolate was K. pneumoniae and the most common resistance mechanism was Klebsiella pneumoniae (K. pneumoniae) carbapenemases (KPC). High susceptibility rates to amikacin and chloramphenicol were also noted. Conclusions: This study reaffirmed the importance of CPE screening and infection control measures. The observed antibiotic susceptibility profile suggests amikacin and chloramphenicol as potential treatments for CPE infection.